Kajian Kriminologi dan Hukum Pidana terhadap Perilaku Vigilantisme pada Masyarakat - Beridiansyah Beridiansyah (Wajah Hukum, 2019)
The ongoing construction companies currently carry a wide range of impacts both positive or negative influence, these effects also impacted the habits on society in addressing any social problems that happen to be settled quickly and instantly, so the imposition of the will is not uncommon accompanied by acts of violence in the form of vigilantism and perform other unlawful acts by ignoring the presumption of innocence that we have adopted in the law enforcement system in our country. The purpose of writing this journal to find the cause of vigilantism on society. To know more about this then vigilantism in question is what is meant by vigilantism and crime and how the approach of criminology and criminal law against vigilantism. Act of vigilantism is a form of public disappointment against careless law enforcement agencies in addressing the problems faced by the community